2011
DOI: 10.1007/s00431-011-1631-2
|View full text |Cite
|
Sign up to set email alerts
|

Complete and incomplete Kawasaki disease: two sides of the same coin

Abstract: Complete and incomplete KD appear to be different sides of the same coin, differing only in the number of signs and symptoms at presentation. Similar laboratory findings and coronary artery outcomes between the two groups support this conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
70
4
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 25 publications
16
70
4
3
Order By: Relevance
“…This distribution of clinical signs was reported that in the previous studies. 16,21 In our study as well, these changes were also less commonly observed in incomplete KD. In the present study gastrointestinal symptoms, sterile pyuria and arthralgia were found as non-classical signs which are consistent with the findings of Yun et al and Manlhiot et al who demonstrated abdominal pain, vomiting, diarrhea, and Majority of the children had raised WBC (75%), raised ESR (95%), increased platelet count (70%) and elevated CRP (75%).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This distribution of clinical signs was reported that in the previous studies. 16,21 In our study as well, these changes were also less commonly observed in incomplete KD. In the present study gastrointestinal symptoms, sterile pyuria and arthralgia were found as non-classical signs which are consistent with the findings of Yun et al and Manlhiot et al who demonstrated abdominal pain, vomiting, diarrhea, and Majority of the children had raised WBC (75%), raised ESR (95%), increased platelet count (70%) and elevated CRP (75%).…”
Section: Discussionsupporting
confidence: 80%
“…15 However, this proportion is higher compared to the incidence (20%) reported by several other studies. 16 Published AHA guidelines, including supplementary laboratory criteria as well as the use of echocardiography, result in better recognition of KD. 17 Regarding patients' age and sex, our study showed the similar complete and incomplete KD groups (p = 0.450 and 0.535 respectively) as compared to that with the findings of Gorczyca et al (2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sudo et al 5,8 indicated the presence of CAD in an echocardiography as a mandatory criterion for incomplete KD, so 100% of cases of incomplete KD had CAD. Manlhiot et al 5,9 defined incomplete KD as fever for ≥5 days and 2 or 3 of the standard criteria, disregarding echocardiographic findings. A similar CAD incidence was found in patients with complete KD.…”
Section: Discussionmentioning
confidence: 99%
“…Incomplete Kawasaki disease is defined as fever lasting 5 days but accompanied by less than 4 diagnostic signs [9]. Atypical Kawasaki disease is diagnosed in a patient who fulfils the diagnostic criteria if the overall clinical presentation is not typical for Kawasaki disease, e.g.…”
Section: Introductionmentioning
confidence: 99%